Assessing ant diversity with bioindicators in a deactivated iron mine: implications for environmental monitoring and recovery efforts - W. L. P. Silva; D. L. Braga; K. A. Santos; J. Barbosa; A. Santos; R. Zanetti (Brazilian Journal of Biology)
Abstract Mining causes serious environmental damage. Monitoring and restoring mined areas mitigate the impacts caused by mining, and ants are organisms that can be used as bioindicators. Their composition is an excellent method for monitoring environmental conditions. The objective of this study was to describe the diversity of ants in an iron mine that was deactivated ten years ago and to verify the ecological variables that explain this diversity. Ants were collected with pitfall epigeic traps with fish and honey in a mining area in the process of environmental recovery after ten years, and three habitats neighbors of the mine: Brazilian Cerrado, Atlantic Forest, and Campo Rupestre. Environmental variables related to vegetation structure were collected to explain the difference in species composition of all habitats. We collected 84 morphospecies of ants belonging to 23 genera and seven subfamilies. Species richness did vary among the area regeneration with grassy and Campo Rupestre. The composition of ants differed between habitats. The mining area regeneration with grassy was characterized by general species and adapted to disturbed environments. We recommend that the recovery plans must focus on reintroducing native plant species, recovering the vertical structure of the vegetation, and on continuous, long-term monitoring to adjust strategies over time.